Fire resistance of external LSF walls with corrugated steel cladding. (January 2022) - Pancheti, Jashnav; Mahendran, Mahen; Steau, Edward
Abstract : Graphical abstract: Abstract : Highlights: Used thin profiled steel cladding as a lightweight cladding replacement for combustible ACPs in LSF buildings. Standard fire tests of two external LSF walls showed significant fire resistance improvement due to steel cladding. Conducted accompanying thermal property tests of two types of Earthwool insulation (glass fibre). Evaluated total R -values of external LSF walls using THERM to understand the implication of insulation location. Replacing cavity insulation with external insulation enhanced both fire and energy performance. Abstract: This paper presents the details of full-scale standard fire tests of external light-gauge steel-framed (LSF) walls with corrugated steel cladding exposed to fire on the external side. Corrugated steel cladding of 0.42 mm thickness is generally used in roof and wall systems of buildings. In this study, it is used as the wall cladding of external LSF walls and as a lightweight cladding replacement to the combustible aluminium composite panels. A detailed investigation was undertaken to evaluate and understand the fire and energy performance of corrugated steel clad external LSF walls, which included (a) thermal property tests of two different types of Earthwool insulation (glass fibre insulation) used in wall systems, (b) full-scale (3 m × 3 m) load bearing standard fire tests of two external LSF wall systems – first with cavity insulation and the second with external insulation and (c) THERM modelling of the tested walls. Steel cladding prevented direct exposure of fire on plasterboards and hence delayed the temperature rise and increased the failure time. Overlaps along the vertical edges of steel cladding played a critical role as gaps formed during the tests. The two external LSF wall systems achieved fire resistance levels (FRLs) in excess of two hours (122 min and 158 min) with improvements greater than 40% due to the addition of thin steel cladding. Replacing cavity insulation with external insulation improved the FRL by about 30% and also its effectiveness in terms of energy efficiency.